DEVELOPING ALGORITHMS FOR KNOWLEDGE SYSTEMS DRIVEN BY AI TO SUPPORT PRODUCT DEVELOPMENT IN THAI LOCAL COMMUNITIES - Buakanok, Fisik Sean; Fongkanta, Pongwat (Journal of Education and Innovation, 2025)
This study explores the implementation of artificial intelligence (AI) algorithms for personalized product development education in Thai rural communities. The research addresses skill deficiencies, promotes economic growth, and enhances educational accessibility through tailored learning experiences. Employing a One-Shot Case Design, the study engaged 50 volunteer participants from the Sop Prap Subdistrict, utilizing surveys, interviews, opinion questionnaires, and competency assessments for data collection. Analysis encompassed descriptive statistics to evaluate the effectiveness of the proposed AI framework. Experimental results showed that: The AI-driven personalized learning approach made education more effective and enjoyable for learners in rural Thai communities. By tailoring the educational experience to each learner's unique needs and preferences, the AI framework improved retention of product development knowledge and skills, ultimately enhancing the quality of locally produced goods. The study's findings suggest that AI-driven personalized learning could be a valuable tool in bridging the skills gap and promoting economic development in rural areas of Thailand.